The association of the circle of Willis anomaly and risk of stroke in patients with carotid artery disease - Eylem Özaydın Göksu; Pınar Koç; Elif Küçükseymen; Ali Ünal; Fatma Genç; Elif Sarıönder Gencer; Aylin Yaman (Arquivos de Neuro-Psiquiatria)
ABSTRACT The circle of Willis is an important collateral system that maintains perfusion to the stenotic area from the contralateral carotid and basilar artery to the region of reduced brain perfusion. The aim of the present study was to compare the circle of Willis anomaly in patients with unilateral symptomatic and asymptomatic carotid artery disease. Results In this retrospective study, we analyzed 175 patients who presented at our outpatient stroke clinic between January, 2013 and June, 2015 with either unilateral symptomatic or asymptomatic carotid artery disease, and who had had CT angiography imaging performed. Demographic properties, carotid artery stenosis and the anomaly of the circle of Willis was recorded. Conclusion There was no statistically significant difference in patients with symptomatic and asymptomatic carotid artery disease in terms of the anomaly of the circle of Willis.